Manajemen Dana Wakaf Produktif Dalam Meningkatkan Perekonomian Masyarakat (Studi Kasus Di Bank Wakaf Mikro Pondok Pesantren Mawaridussalam) - Melisa Zuriani Hasibuan; Munawaroh Munawaroh; Rizqy Fadhlina Putri; Henny Andriyani Wirananda (AGHNIYA : Jurnal Ekonomi Islam, 2026)
This study aims to analyze the management of productive waqf funds in enhancing community welfare at the Micro Waqf Bank (BWM) of Pondok Pesantren Mawaridussalam. Employing a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation. Data validity was ensured using source triangulation, technique triangulation, and member checks. The findings indicate that waqf fund management is conducted through four management functions (POAC): planning using the qardhul hasan scheme, organizing operational structures, implementing group-based financing with weekly mentoring, and controlling through regular meetings and reports. Challenges include limited human resource capacity, manual bookkeeping, and low financial literacy among beneficiaries. Strategic solutions include regular training, digitizing the reporting system, and strengthening spiritual values rooted in pesantren culture. The study concludes that systematically managed waqf funds, based on Islamic principles, significantly contribute to empowering the local community’s economy.